Engaging Volunteers through ISOTURES: Selecting for Volunteer Involvement - Andrew Toelle; Sophia Cooney; Lori Wiggins (EDIS)
This is the Selection portion of the ISOTURE volunteer management model, part of the Engaging Volunteers through ISOTURES series. This 3-page publication discusses in detail the selection process for volunteers in Florida 4-H. Major revision by Andrew Toelle, Sophia Cooney, and Lori Wiggins. https://edis.ifas.ufl.edu/4h303